Blood product transfusion and mortality in neonatal extracorporeal membrane oxygenation. Issue 2 (14th December 2019) - Keene, Sarah D.; Patel, Ravi Mangal; Stansfield, Brian K.; Davis, Joel; Josephson, Cassandra D.; Winkler, Anne M.
Abstract : BACKGROUND: Neonates receiving extracorporeal membrane oxygenation (ECMO) support are transfused large volumes of red blood cells (RBCs) and platelets (PLTs). Transfusions are often administered in response to specific, but largely unstudied thresholds. The aim of this study is to examine the relationship between RBC and PLT transfusion rates and mortality in neonates receiving ECMO support. STUDY DESIGN AND METHODS: We retrospectively examined outcomes of neonates receiving ECMO support in the neonatal intensive care unit (NICU) for respiratory failure between 2010 and 2016 at a single quaternary‐referral NICU. We examined the association between RBC and PLT transfusion rate (mL per kg per day) and in‐hospital mortality, adjusting for confounding by using a validated composite baseline risk score (Neo‐RESCUERS). RESULTS: Among the 110 neonates receiving ECMO support, in‐hospital mortality was 28%. The median RBC transfusion rate (mL/kg/d) after cannulation was greater among non‐survivors, compared to survivors: 12.4 (IQR 9.3‐16.2) versus 7.3 (IQR 5.1‐10.3), p < 0.001. Similarly, PLT transfusion rate was greater among non‐survivors: 22.9 (9.3‐16.2) versus 12.1 (8.4‐20.1), p = 0.02. After adjusting for baseline mortality risk, both RBC transfusion (adjusted relative risk per 5 mL/kg/d increase: 1.33; 95% CI 1.05‐1.69, p = 0.02) and PLT transfusion (adjusted relative risk per 5 mL/kg/d increase: 1.12; 95% CI 1.02‐1.23, p = 0.02) were both associated with in‐hospital mortality. CONCLUSIONS: RBC and PLT transfusion rates are associated with in‐hospital mortality among neonates receiving ECMO. These data provide a basis for future studies evaluating more restrictive transfusion practices for neonates receiving ECMO support.